Are centenarians genetically predisposed to lower disease risk? - Ruiz, Jonatan R. (Springer Netherlands, 2011)
Our study purpose was to compare a disease-related polygenic profile that combined a total of 62 genetic variants among (i) people reaching exceptional longevity, i.e., centenarians (n = 54, 100–108 years, 48 women) and (ii) ethnically matched healthy controls (n = 87, 19–43 years, 47 women). We computed a ‘global’ genotype score (GS) for 62 genetic variants (mutations/polymorphisms) related to cardiometabolic diseases, cancer or exceptional longevity, and also specific GS for main disease categories (cardiometabolic risk and cancer risk, including 36 and 24 genetic variations, respectively) and for exceptional longevity (7 genetic variants). The ‘global’ GS was similar among groups (centenarians: 31.0 ± 0.6; controls 32.0 ± 0.5, P = 0.263). We observed that the GS for hypertension, cancer (global risk), and other types of cancer was lower in the centenarians group compared with the control group (all P < 0.05), yet the difference became non significant after adjusting for sex. We observed significant between-group differences in the frequency of GSTT1 and GSTM1 (presence/absence) genotypes after adjusting for multiple comparisons. The likelihood of having the GSTT1 low-risk (functional) allele was higher in centenarians (odds ratio [OR] 5.005; 95% confidence interval [CI], 1.810–13.839), whereas the likelihood of having the GSTMI low-risk (functional) allele was similar in both groups (OR 1.295; 95% CI, 0.868 –1.931). In conclusion, we found preliminary evidence that Spanish centenarians have a lower genetic predisposition for cancer risk. The wild-type (i.e., functional) genotype of GSTT1, which is associated with lower cancer risk, might be associated with exceptional longevity, yet further studies with larger sample sizes must confirm these findings.